2016
DOI: 10.1080/19440049.2016.1263876
|View full text |Cite
|
Sign up to set email alerts
|

Residue depletion of oxytetracycline (OTC) and 4-epi-oxytetracycline (4-epi-OTC) in broiler chicken’s claws by liquid chromatography-tandem mass spectrometry (LC-MS/MS)

Abstract: Antibiotics are widely used in poultry production for the treatment of bacterial diseases. However, residues may remain in products and by-products destined for human consumption or animal feeding. The claws of chickens, which are a by-product of the poultry industry, can directly or indirectly enter the food chain as meals destined to feed other productive animals. Thus, it becomes necessary to determine and quantify antimicrobial residues present in this matrix. The objective of the study was to assess the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…This situation was also reported by Cornejo et al [ 42 ], who found that OTC and 4-epi-OTC residues could still be quantified in feathers by day 46 after ceasing treatment. Moreover, withdrawal periods for OTC and 4-epi-OTC in chicken claws have been established at 39 and 54 days, respectively, hence surpassing even the age of slaughter that is currently practiced by the poultry industry [ 44 ]. Such evidence suggests that finding these elevated concentrations of CTC and 4-epi-CTC in chicken droppings on the last sampling day (as well as the observation that concentrations increased on day 21 and 25), could be attributed to the systemic recirculation of these residues from feathers and claws.…”
Section: Discussionmentioning
confidence: 99%
“…This situation was also reported by Cornejo et al [ 42 ], who found that OTC and 4-epi-OTC residues could still be quantified in feathers by day 46 after ceasing treatment. Moreover, withdrawal periods for OTC and 4-epi-OTC in chicken claws have been established at 39 and 54 days, respectively, hence surpassing even the age of slaughter that is currently practiced by the poultry industry [ 44 ]. Such evidence suggests that finding these elevated concentrations of CTC and 4-epi-CTC in chicken droppings on the last sampling day (as well as the observation that concentrations increased on day 21 and 25), could be attributed to the systemic recirculation of these residues from feathers and claws.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 4-epi-oxytetracycline and N-demethyloxytetracycline were detected as metabolites of oxytetracycline in egg and hen plasma [11]. In another study, 4-epioxytetracycline was also detected in bones (femur, breastbone, fibula, and tibia) from broilers treated with oxytetracycline [12]. In addition, several metabolites were detected as a result of abiotic degradation of oxytetracycline in the soil, including 4-epi-oxytetracycline, α-apo-oxytetracycline, and β-apo-oxytetracycline [13].…”
Section: Discussionmentioning
confidence: 96%
“…In those studies, they analyzed samples of muscle and bone tissues from broiler chickens who were treated with a therapeutic dose of a 20% oxytetracycline formulation, concluding that their bones evidenced a high bioaccumulation of oxytetracycline in them. Not long after, Cornejo et al [ 10 ] assessed the depletion of oxytetracycline in claws from broiler chickens who received a diet containing a commercial formulation of this drug. These authors found high concentrations of oxytetracycline residues, and these drugs persisted for longer periods than the established withdrawal time for that specific formulation in muscle tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, studies examining bioaccumulation of veterinary drugs in chicken claws are scarce. One of them [ 10 ] explored the behavior of oxytetracycline (OTC) and its active metabolite (4-epi-oxytetracycline) in broiler chicken claws treated with a therapeutic dose of 10% OTC. By day 3 after ceasing treatment, they quantified concentrations of 2997 µg·kg −1 for both OTC and 4-epi-OTC.…”
Section: Introductionmentioning
confidence: 99%